The role of events in local development: An analysis of residents' perspectives and visitor satisfaction. (February 2021) - Fytopoulou, Eleftheria; Tampakis, Stilianos; Galatsidas, Spyridon; Karasmanaki, Evangelia; Tsantopoulos, Georgios
Abstract: Tourism is arguably one of the most promising options for economic prosperity in rural areas. Effective strategies aiming at tourism development, however, should be based on a thorough analysis of residents' preferences as well as visitors' expectations and satisfaction. Hence, the aim of this paper is to investigate residents' views on tourism development and the contribution of various productive sectors to local development as well as to examine event visitors' views and satisfaction level in a rural area in Greece. Results based on quantitative data collected via questionnaires showed that the residents perceived that nature-based types of tourism should be developed and preferred Greek rather than foreign investors to be involved in tourism development. Moreover, the majorities of visitors attending events regarded the study area as a value-for-money destination and experienced positive emotions during their stay. In addition, half of visitors attending a Christmas event expressed their willingness to attend the event again in the future whereas most film festival visitors were significantly less willing to do so. Moreover, the visitors of all events were highly satisfied with the natural environment in the destination. Finally, it may be concluded that events are able to establish areas as value-for-money destinations and to contribute to local development. The results presented in this paper may be particularly useful to local authorities and stakeholders involved in the development of tourism in rural areas both in Greece and elsewhere. Highlights: Residents preferred tourism types related to nature to be developed in their region. Greek rather than foreign investors were favored by residents. Drama was perceived by most visitors as a value-for-money destination. The local natural environment received the highest rating from all visitor categories. Most visitors experienced positive feelings during their visit in Drama.